Hybrid in vitro diffusion cell for simultaneous evaluation of hair and skin decontamination: temporal distribution of chemical contaminants. Issue 1 (December 2018) - Matar, Hazem; Amer, Nevine; Kansagra, Sneha; Pinhal, Andreia; Thomas, Elliot; Townend, Scott; Larner, Joanne; Chilcott, Robert
Abstract Most casualty or personnel decontamination studies have focused on removing contaminants from the skin. However, scalp hair and underlying skin are the most likely areas of contamination following airborne exposure to chemicals. The aim of this study was to investigate the interactions of contaminants with scalp hair and underlying skin using a hybridin vitro diffusion cell model. Thein vitro hybrid test system comprised "curtains" of human hair mounted onto sections of excised porcine skin within a modified diffusion cell. The results demonstrated that hair substantially reduced underlying scalp skin contamination and that hair may provide a limited decontamination effect by removing contaminants from the skin surface. This hybrid test system may have application in the development of improved chemical incident response processes through the evaluation of various hair and skin decontamination strategies.